The effect of incentive factors on turnover intention of PHC workforce in rural China-from the perspective of two-factor theory - Lingzhi Sang; Xin Zheng; Guimei Chen; Zhongliang Bai; Ren Chen (BMC, 2024)
Abstract Objective The working situation and turnover intention of rural primary healthcare(PHC) workforce have always been of concern. This study aims to explore the effect of different incentive factors on turnover intention of PHC Workforce, with the goal of optimizing health human resources in China. Methods Structured questionnaires were used for data collection, including incentive factors questionnaire based on two-factor theory, turnover intention, perceived social support and job burnout. Multiple linear regression was used to analyze the influence of different incentive factors on turnover intention. Structural equation model was used to explore the effect of motivation factors on turnover intention through different paths of job burnout and social support. Results The total number of participants was 1112. PHC Workforce scored higher on hygienic factors than on motivation factors, both of which showed moderate satisfaction levels and the turnover intention level was below average. In regression analysis, the factors related to turnover intention included individual status (B =-0.854), salary (B =-0.610), individual progress (B =-0.628), education level (B = 0.971), monthly income (B =-0.161) and marital status (B = 1.664). The indirect effects of different types of incentive factors through social support were 0.097 (P < 0.001), 0.045 (P < 0.001), and 0.136 (P < 0.001). Conclusion Different incentive factors may decrease turnover intention of PHC Workforces, which is reflected in three key factors: individual status, salary, and individual progress. The mediating effect of social support is significant, suggesting that managers should prioritize staff mental health and family relationships. Also, implementing diverse incentive strategies and addressing individual needs.